A survey‐based study concerning public comprehension of two‐component EXIT/NO‐EXIT signage concepts. (9th October 2021) - Xie, Hui; Galea, Edwin R.
Summary: Emergency signage conveys exit route information enabling occupants to identify and utilise emergency exits during evacuation. However, it has been frequently demonstrated that static signs are insufficient to attract people's attention. Previous incidents also demonstrate that if exit routes and exits become compromised by the incident, static signs are unable to adapt as required. A goal of the signage industry is to address these limitations while maintaining the clear and unambiguous information conveyed. A signage concept addressing these limitations incorporating a pair of linked adjacent signs, a standard EXIT sign and a text‐based 'NO‐EXIT' sign, is proposed. At any one time, only one sign is activated, displaying either EXIT or NO‐EXIT. The active sign can also flash to improve detectability. To assess whether this concept was acceptable, an online international survey, based on the ANSI Z535.3 comprehension test methodology was conducted. The results demonstrate that this novel concept fails to meet the acceptance criteria for safety signs, and as a result, the concept was abandoned by the manufacturer. This study also highlights the importance of conducting comprehension tests for any new safety signage design and the need for composing guidelines for design and application of dynamic signs.